2019
DOI: 10.1186/s41100-019-0233-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with gustatory threshold for salty taste in peritoneal dialysis patients

Abstract: Background: Taste disorder is a common problem in patients with chronic kidney disease and end-stage renal disease. Specifically, salty taste disorder is associated with excess salt intake. Many factors affect taste activity; however, data focused on peritoneal dialysis (PD) patients are limited. This study aimed to investigate the distribution of the gustatory threshold for salty taste and to clarify its relevant contributing factors in PD patients. Methods: In this retrospective cross-sectional study, we enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Then they were asked to place a strip saturated with salt chloride on their tongue for 3 s. The lowest concentration at which participants identified the salt taste was taken as the recognition threshold. Participants who could not recognize taste, even at the highest concentration level (1.6 mg/cm 2 ), were assigned 1.8 [22].…”
Section: Salt Taste Sensitivitymentioning
confidence: 99%
“…Then they were asked to place a strip saturated with salt chloride on their tongue for 3 s. The lowest concentration at which participants identified the salt taste was taken as the recognition threshold. Participants who could not recognize taste, even at the highest concentration level (1.6 mg/cm 2 ), were assigned 1.8 [22].…”
Section: Salt Taste Sensitivitymentioning
confidence: 99%
“…In the elderly, Kubota et al (2018) also found that the estimated of daily salt intake based on 24-hour urinary sodium excretion would increase according to the high STT. But, different results found that sodium urine excretion in the elderly is lower in high STT (Torigoe et al, 2019). The results might be differences because of measurement methods and participant conditions.…”
Section: Salt Taste Threshold Salt Intake and Blood Pressurementioning
confidence: 90%
“…Fourteen studies that examined STT and hypertension had an age between 18 -78 years. The most age categories are old adults with an average age of more than 45 years (Amen, 2015;Azotea, Cruz, & Barcelon, 2013;Cho, Kim, Jeong, & Kim, 2016;Kim, Ye, & Lee, 2017;Piovesana et al, 2013;Son et al, 2015;Veček et al, 2020), followed by young adults or 17-30 years old (Martinelli, Conde, de Araújo, & Marcadenti, 2020;Tjahajawati, Rafisa, Murniati, & Zubaedah, 2020), middle-age adults or 31-45 years old (Adolf et al, 2021;Fayasari & Cahyani, 2022, and elderly or up to 60 years old (Kubota et al, 2018;Torigoe et al, 2019;Xue et al, 2020).…”
Section: Subject Characteristicmentioning
confidence: 99%
See 2 more Smart Citations